Primeval Germany: Nazism through beast, blood, and soil in the 19th and 20th centuries - Allen, Ryon (2023)
The ideal German, Arminius, that became mythologized in the nineteenth century was immortalized at the top of Grotenburg Hill. Arminius’s bronze statue symbolizes all of Germany’s victories against foreign invaders who wanted to disrupt German culture and environment. The statue is wielding a sword that points towards France and a dead eagle under one foot. It is through the mythology of Arminius that propels Germans of the twentieth century to hark back to a primeval Germany. This sentiment is carried through the Second World War by the Nazis, specifically of major concern to Hermann G?ring and Heinrich Himmler. Nazi environmental practices through these men, centered around the ideal notions of blood, soil, and beast. Out of the three, beasts would prove to be the most important and most difficult to accomplish. G?ring’s ideal German beast is the extinct primeval cattle, aurochs. Through aurochs, the Nazi environmental programs and policies that were put in place would culminate into an ideal Germany made up of German beasts, forests, and blood. The current scholarship surrounding Nazi environmental policies focuses mainly on two aspects of the trifecta, forests, and blood. In order to further understanding on the Nazi’s fascination and mythologization of the environment, the key factor is analyzing the three points in congruence with each other and not as separate entities.